Analysis of Supply Chain Management Strategy in Increasing Responsiveness to Market Changes (Case Study: UD Rahmad Loyang) - Annisa, Annisa; Safrizal, Safrizal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the implementation of Supply Chain Management (SCM) strategies at UD Rahmad Loyang in enhancing responsiveness to market changes. The research employed a descriptive qualitative approach through interviews, observations, and documentation. The findings show that inventory management is carried out manually through daily monitoring, while product distribution follows predetermined routes and schedules to three branches of Irian Supermarket. The company demonstrates a relatively good level of responsiveness to fluctuating demand, as reflected in its ability to increase orders during high-demand periods. However, this responsiveness is not yet optimal due to the absence of modern forecasting systems and digital inventory management. Several issues were identified, including dependence on certain suppliers, manual stock recording, and suboptimal distribution routes. This study recommends adopting digital inventory systems, implementing data-based forecasting, diversifying suppliers, optimizing distribution routes, and applying lean distribution practices.